10. EFFECTIVENESS OF SUPPLEMENTING THE NUTRITIONAL PRODUCT LEANMAX BONE ON THE HEALTH AND BONE HEALING OF PATIENTS WITH BONE FRACTURES (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluating the intervention effectiveness of the nutritional product Leanmax Bone in patients with post-traumatic fractures.Research objects and methods: The randomized controlled intervention study. The sample size of 120 patients post-traumatic closed fracture was randomly divided into 2 similar groups: 60 patients were interventionally supplemented Leanmax Bone with a content of 40 grams/time, 2 times/day and 60 patients in the control group with normal nutrition. Collect and analyze data according to research indicators using SPSS20.0 software.Results: After 8 weeks, the intervention group had level III bone healing 38.3% higher than the control group (91.7% vs. 53.3%) (p < 0.05); good treatment results are 48.3% higher (78.3% vs. 30%) (p < 0.05); diarrhea rate was 18.3% lower (5% vs. 23.3%) (p < 0.05); bloating/indigestion was 36.7% lower (3.3% vs. 40%) (p < 0.05); no constipation. Inflammation/infection at the trauma area (3.3%), respiratory tract infection (1.7%), use of additional antibiotics (10%), and urinary tract infection (0%) were all lower control group with p < 0.05. Weight loss rate was 26.7% lower (33.3% vs. 60%), malnutrition and risk of malnutrition were 28.3% lower (p < 0.05), numbness in limbs/mouse withdrawal was 40% lower (p < 0.05), skin itching was 61.7% lower (p < 0.05). The rates of anorexia (10%), nausea (1.7%), and difficulty sleeping (11.7%) were also lower than the control group with p < 0.05. 78.3% of patients were very satisfied; 16.7% are satisfied and 5% are satisfied with the product.Conclusion: Supplementing Leanmax Bone has accelerated bone healing, improved treatment results and mobility, enhanced immunity and reduced trauma infections, improved digestion, nutrition and health post-traumatic closed fracture patients fare better than the control group. High product acceptance rate.
Keywords: bone healing; immunity system; nutrition; multi-micronutrients